Gestión de logística y control de inventarios de la Importadora JORUA CÍA. LTDA. - sucursal Babahoyo - Ronquillo Murrieta, Fernando Eduardo (2019)
Currently, companies must be firmly anchored in the commercial vanguard and adapt to various factors such as social and technological changes that directly influence the operational and productive structure of each of them. Efficiently adapt your production processes and logistics is a key point, to stay competitive and not decline in the markets as a company